The impact of the jurisprudence of the Inter- American Court on the European Court of Human Rights - Díaz Crego, María (2015)
The reciprocal influence between the Inter-American Court andthe European Court of Human Rights has been analysed by several studies that have focused on the impact of the European case- law in its Inter- American counterpart. In this context, this paper aims to pay attention to the reverse phenomenon. Therefore, it studies the decisions in which the European Court of Human Rights has explicitly referred to the Inter-American Court’s case law. By doing so, it attempts to elucidate the subject areas in which the European Court is most influenced by its Inter-American counterpart and the extent of this influence.